Somato-Regulatory Imbalance as a Pathophysiological Basis of Civilization Diseases: A Systematic Review and Meta-Analysis - Gozhenko, Anatoliy; Gozhenko, Olena; Zukow, Walery; Pavlega, Hanna (Journal of Education, Health and Sport, 2025)
Objective: To conduct a systematic literature review on the role of somato-regulatory imbalance in the pathogenesis of civilization diseases and evaluate the effectiveness of therapeutic interventions. Methods: We searched PubMed, Embase, Cochrane Library, and Web of Science databases for the period 2000-2025. PRISMA 2020 criteria and Cochrane Handbook methodology were applied. A meta-analysis of homogeneous studies was performed using a random-effects model. Results: We identified 2,847 potentially relevant publications, of which 127 met inclusion criteria (34 RCTs, 58 cohort studies, 23 cross-sectional studies, and 12 systematic reviews). The meta-analysis showed that the combination of chronic psycho-emotional stress and reduced physical activity increases cardiovascular disease risk by 2.8-fold (RR = 2.80; 95% CI: 2.34-3.35), type 2 diabetes by 2.1-fold (RR = 2.12; 95% CI: 1.78-2.52), and metabolic syndrome by 3.2-fold (RR = 3.21; 95% CI: 2.67-3.86). Conclusions: Somato-regulatory imbalance represents a key pathophysiological mechanism of civilization diseases, requiring a comprehensive approach to prevention and treatment that considers both somatic and regulatory components.